Gut microbiome modulates efficacy of immune checkpoint inhibitors - Yi, Ming (J Hematol Oncol, 2018)
Immune checkpoint inhibitors (ICIs) therapy is a novel strategy for cancer treatments in recent years. However, it was observed that most patients treated with ICIs could not get benefit from the therapy, which led to the limitation of clinical application. Motivated by potent and durable efficacy of ICIs, oncologists endeavor to explore the mechanisms of resistance to ICIs and increase the drug sensitivity. It is known that heterogeneity of gut microbiome in populations may result in different outcomes of therapy. In xenograft model, bacteria in gut have been proved as a crucial factor regulating immunotherapy efficacy. And the similar phenomenon was obtained in patients. In this review, we summarized relevant advancements about gut microbiome and ICIs. Furthermore, we focused on modulatory function of gut microbiome in ICIs therapy and possible antitumor mechanism of specific commensals in ICIs treatment. We propose that gut microbiome is an important predictive factor, and manipulation of gut microbiome is feasible to elevate response rate in ICIs therapy.